NEW SPECIES IN OLD WORLD BOEHMERIA (URTICACEAE) - Wilmot-Dear, C. M.; Friis, I.; Thomas, Z. (Edinburgh Journal of Botany, 2010)
Four new species of Boehmeria (Urticaceae) are described and named: Boehmeria listeri Friis & Wilmot-Dear and B. manipurensis Friis & Wilmot-Dear from the eastern part of the Himalayas, B. leptostachya Friis & Wilmot-Dear from southern China (Yunnan), Thailand and northern Sumatra, and B. subintegra Friis & Wilmot-Dear from Papua New Guinea. The species are illustrated and mapped and their habitat ranges are described, and conservation assessments have been produced for all.
Keywords: Boehmeria; Boehmeria leptostachya; Boehmeria listeri; Boehmeria manipurensis; Boehmeria subintegra; China; description; Himalayas; New Guinea; species; Sumatra; taxonomy; Thailand; Urticaceae